Explorations : - Arny, Thomas T. (McGraw-Hill, 2004)
Written in a clear, concise style for the non-science major, this edition uses analogies and everyday examples to present the most current information about astronomy in a way that students can easily understand. It comes packaged with a free interactive CD-ROM and has a new, expanded web site.